1989
DOI: 10.1073/pnas.86.4.1307
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T4 DNA topoisomerase is the target of antitumor agent 4'-(9-acridinylamino)methanesulfon-m-anisidide (m-AMSA) in T4-infected Escherichia coli.

Abstract: The mammalian type II DNA topoisomerase has been proposed to be the intracellular target of a variety of antitumor agents, including m-AMSA [4'-(9-acridinylamino)-methanesulfon-m-anisidide]. Because the bacteriophage T4-encoded topoisomerase resembles the mammalian enzyme, we are using T4 as a simple model system to investigate the mechanism of action of m-AMSA. A mutation that renders T4 growth m-AMSA-resistant is closely linked to an amber mutation in T4 gene 39, which encodes one of the topoisomerase subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The antitumor drug m-AMSA blocks T4 growth by targeting the phage-encoded type II topoisomerase (31). Nevertheless, this enzyme is not essential for T4 DNA replication, presumably because the host DNA gyrase can substitute for it (45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor drug m-AMSA blocks T4 growth by targeting the phage-encoded type II topoisomerase (31). Nevertheless, this enzyme is not essential for T4 DNA replication, presumably because the host DNA gyrase can substitute for it (45).…”
Section: Resultsmentioning
confidence: 99%
“…Phage T4 encodes a type II DNA topoisomerase that is inhibited by many of the same antitumor drugs that block the mammalian enzyme. The T4 topoisomerase was demonstrated to be the physiological target for m-AMSA (31), and inhibition of phage growth is probably dependent on cleavage complex formation (see above) (50). Recombinational repair of damage derived from the drug-induced cleavage complex is important in both the bacteriophage T4 and mammalian systems, which also argues that T4 is a useful model system for these studies.…”
mentioning
confidence: 99%
“…A new restriction enzyme polymorphism was found in the resistant forms. A mutation at the ATP binding site has been found to induce mAMSA resistance in the bacteriophage T4 DNA topoisomerase (42,43). The extent to which downregulation of the total amount of top0 I1 is a significant resistance mechanism remains unclear, although reduced levels of top0 I1 shown in some studies could be due to decreased half-life of the mutant protein.…”
Section: Topoisomerase I1 and Drug Resistancementioning
confidence: 99%
“…Most importantly, both are sensitive to the aminoacridine m-AMSA [4'-(9-acridinylamino)methanesulfon-m-anisidide] (10, 11). A point mutation in one of the genes encoding the bacteriophage T4 topoisomerase allows drug-resistant phage growth, and topoisomerase purified from the mutant phage has drug-resistant topoisomerase activity (12,13).Topoisomerase inhibitors convert the enzymes that they target into poisons by inducing formation of the cleavage complex, a form of DNA damage. This view was first articulated when it was found that bacteriophage 17 …”
mentioning
confidence: 99%
“…Most importantly, both are sensitive to the aminoacridine m-AMSA [4'-(9-acridinylamino)methanesulfon-m-anisidide] (10,11). A point mutation in one of the genes encoding the bacteriophage T4 topoisomerase allows drug-resistant phage growth, and topoisomerase purified from the mutant phage has drug-resistant topoisomerase activity (12,13).…”
mentioning
confidence: 99%